[2]Pseudorotaxane formation with fret based luminescence response: demonstration ofboolean operations through self sorting on solid surface - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Das, Amitava (Journal of Organic Chemistry, 2016)
Binary pseudorotaxane formation between an aza crown derivative as host (H) and two different imidazolium derivatives as guests (G(1) and G(2)) have been studied in detail by NMR (H-1 NMR, 2D NOESY), optical (steady state electronic and emission spectroscopy), and mass spectroscopy. Binding stoichiometry (1:1), association constant for the respective [2]pseudorotaxane formation (K-a(H center dot G1) = (2.61 +/- 0.015) X 10(3) M-1 and K-a(H center dot G2) = (1.27 +/- 0.16) X 10(3) M-1), and associated thermodynamic parameters are also evaluated based on isothermal titration calorimetric (ITC) studies. FRET based luminescence ON responses are observed on formation of the binary pseudorotaxane (H center dot G(1) and H center dot G(2)) in a nonpolar medium like dichlororriethane. The thermodynamic feasibility of such an energy transfer process is also examined. The higher affinity of H and 18-crown-6 toward K+, as compared to those toward G(1) or G(2), and the reversibility in the host- guest binding process are utilized in demonstrating the self-sorting phenomena with associated changes in luminescence responses that could be correlated for Boolean operators like YES, INHIBIT, OR, and AND gates.

Chiral discrimination through h-1 nmr and luminescence spectroscopy: dynamic processes and solid strip for chiral recognition - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Rajamohanan, P. R.; Ravindranathan, Sapna; Das, Amitava (Chemistry-A European Journal, 2017)
The appropriate choice of the host molecules with well-defined optical activity (S-H/R-H) helps in the differentiation between two secondary ammonium ion-derivative guest molecules with different optical activities (R-G/S-G) based on the fluorescence resonance energy transfer (FRET)based luminescence responses. Crown ether-based host molecules with opposite chiral configurations (R-H, S-H) have been derived from 1,1'-bi-2-naphthol (BINOL) derivatives that have axially chiral biaryl centers. These chiral crown ethers form host-guest complexes (i.e., [2] pseudoro-taxanes) with chiral secondary ammonium ion derivatives (R-G, S-G). NMR spectroscopic studies show that the complexes are in a dynamic equilibrium in solution. Results of the H-1 NMR and fluorescence spectroscopic studies indicate a head-on orientation of the host and guest in the [2] pseudorotaxanes. The difference in the efficiency in the FRET-based responses between anthracene and the BINOL derivatives allow efficient chiral discrimination of the guests. Isothermal titration calorimetry and NMR investigations reveal that inclusion complexes between hosts and guests of the same chirality (R-H center dot R-G, S-H center dot S-G) are more stable relative to those of opposite chirality (R-H center dot S-G, S-H center dot R-G). However, FRET-based energy-transfer efficiency is higher for R-H center dot S-G and S-H center dot R-G complexes. NMR spectroscopic studies show that the relative orientation of the guest in the host cavity is significantly different when the host binds a guest of the same or opposite chirality; furthermore, the latter is more favorable for FRET, thus enabling discrimination between enantiomers. Interestingly, chiral discrimination of guest ions could also be achieved by using silica surfaces modified with chiral host molecules.

Proton-coupled electron-transfer processes in ultrafast time domain: evidence for effects of hydrogen-bond stabilization on photoinduced electron transfer - Dey, Ananta; Dana, Jayanta; Aute, Sunil; Maity, Partha; Das, Amitava; Ghosh, Hirendra N. (Chemistry-A European Journal, 2017)
The proton-coupled electron-transfer (PCET) reaction is investigated for a newly synthesized imidazoleanthraquinone biomimetic model with a photoactive RuIIpolypyridyl moiety that is covalently coupled to the imidazole fragment. Intramolecular H-bonding interactions between imidazole and anthraquinone moieties favor the PCET process; this can be correlated to an appreciable positive shift in the one-electron reduction potential of the coordinated anthraquinone moiety functionalized with the imidazole fragment. This can also be attributed to the low luminescence quantum yield of the RuII-polypyridyl complex used. The dynamics of the intramolecular electron-transfer (ET) and PCET processes are studied by using femtosecond transient absorption spectroscopy. The steady- state spectroscopic studies and the results of the time- resolved absorption studies confirm that H- bonded water molecules play a major role in both ET and PCET dynamics as a proton relay in the excited state. The electron- transfer process is followed by a change in the H- bonding equilibrium between AQ and imidazole in acetonitrile solvent, and protonation of AQ(-) water leads to PCET in the presence of water. A slower forward and backward electron- transfer rate is observed in the presence of D2O compared with that in H2O. These results provide further experimental support for a detailed understanding of the PCET process.

Impact of half-crown/two carbonyl:-Ca2+ metal ion interactions of a low molecular weight gelator (LMWG) on its fiber to nanosphere morphology transformation with a gel-to-sol phase transition - Maity, Arunava; Dey, Ananta; Si, Mrinal Kanti; Ganguly, Bishwajit; Das, Amitava (Soft Matter, 2018)
We report here a smart functional low molecular weight gelator (LMWG) L, containing an unusual metal ion coordination site, i.e. ``half-crown/two carbonyl''. The gelator L shows excellent gelation behavior with typical fibrillar morphology in acetonitrile, methanol and ethanol media. Upon Ca2+ ion binding with its ``half-crown/two carbonyl'' coordination site, the acetonitrile gel of L exhibits a fiber to nanosphere morphology transformation along with a gel-to-sol phase transition as confirmed by microscopic investigation and by direct naked eye visualization, respectively. The mechanism involved in this morphology transformation and gel-to-sol phase transition process was studied thoroughly with the help of computational calculations and various spectroscopic experiments and discussed.

Water induced morphological transformation of a poly(aryl ether) dendron amphiphile: helical fibers to nanorods, as light-harvesting antenna systems - Maity, Arunava; Dey, Ananta; Gangopadhyay, Monalisa; Das, Amitava (Nanoscale, 2018)
Self-assembly of suitable molecular building blocks is an efficient and convenient approach to generate nanomaterials with various morphologies and functions. Moreover, understanding the nature of molecules and controlling factors of their self-assembly process is crucial in fundamental aspects of molecular self-assembly which provide insights into the design of new assemblies with functional nano-architectures. To this end, the present study reports water induced self-assembled multifaceted morphology formation and the plausible pathway of the morphology transformation of a single poly(aryl ether) dendron amphiphile 1(D). In THF, 1(D) self-assembles into helical fibers. However, with an increase in the water fraction in its THF solution, the morphology changes to nanorods through an intermediate scroll-up pathway of exfoliated fibers. The nanorod formation and transformation of 1(D) are investigated using various microscopy and spectroscopy techniques, which indicate that it has highly ordered multilayered arrays of 1(D) molecules. Finally, these multilayered arrays of 1(D) nanorods are exploited for constructing a model light-harvesting system via the incorporation of small quantities of two newly designed BODIPY based molecules as energy acceptors and 1(D) as an antenna chromophore.

Hydrogen bond assisted photoinduced intramolecular electron transfer and proton coupled electron transfer in an ultrafast time domain using a ruthenium-anthraquinone dyad - Dey, Ananta; Dana, Jayanta; Aute, Sunil; Das, Amitava; Ghosh, Hirendra N. (Photochemical & Photobiological Sciences, 2019)
Quinones play a significant role as primary electron acceptors in the natural photosynthetic system of photosystem II, and their reduction is known to be facilitated by hydrogen-bond donors or protonation. In this study, a ruthenium(ii) polypyridyl complex 1 coupled to an anthraquinone (AQ) functionality through a rigid imidazole (Im) spacer has been synthesized to examine the effect of H-bonding on both the thermal and photoinduced electron transfer reactions. The anthraquinone moiety of complex 1 is fused to a benzi-imidazole system bearing C & xe001;(OMIDLINE)-M-AQ HORIZONTAL ELLIPSISHNIm based H-bonding at one side of the anthraquinone moiety so that intramolecular hydrogen bonding from the imidazole group to the nearby quinone carbonyl can occur. The hydrogen bond formation involving the semiquinone radical anion produced through the photoinduced reduction process in Ru-im-AQ and the imidazole proton in complex 1 resulted in a significant positive shift of one electron reduction potential of complex 1. The kinetics for the formation of the charge-separated states was explored by using femtosecond transient absorption spectroscopy. Hydrogen bonding between water and the reduced anthraquinone accounted for thermodynamic and kinetic stabilization of these charge-separated states. An attempt has been made to assess the relative importance of the driving force and solvent polarity, in the rates of photoinduced electron transfer in complex 1. The 490 nm transient absorption band of anthraquinone radical anions (AQ(-)) and a broad absorption in the 580-750 nm region having maxima at similar to 690 nm have been observed and this is attributed to the generation of a transient Ru3+-species of the corresponding complex 1. Addition of water entails an acceleration of electron transfer rates by a factor of 3.33. The system investigated may serve as a model for the mechanistic diversity of PCET reactions in general with water as a primary proton donor. Furthermore, our studies are relevant for understanding proton-coupled electron transfer (PCET) reactivity of electronically excited states at a fundamental level because changes in hydrogen-bonding strength accompanying changes in redox states may be regarded as a variant form of PCET.